Meningkatkan Hasil Belajar Matematika Peserta Didik Sekolah Dasar Melalui Model Pembelajaran Contextual Teaching and Learning (CTL) - Fitri Yanti Muchtar; Fitri Aulia Nurdin; Kasmawati Kasmawati; Nurwahyuningsih Nurwahyuningsih; Muhammad Yamin; Muhammad Ilham S (Departement of Mathematics Education, 2023)
The goal of this research is to improve the mathematical learning outcomes of grade II students at State Elementary School 32 Tumampua VI through the Contextual Teaching and Learning (CTL) model. This type of research uses the Classroom Action Research method, consisting of two cycles, with procedures that include planning, implementation, observation and reflection. The subjects of the research were 17 grade II students at State Elementary School 32 Tumampua Pa'doang-doangang, consisting of 9 male and 8 female students. Based on the results of the research, the discussion and data analysis shows that the average score of the learning outcomes in cycle 1 was 67.52, and in cycle II it increased to 86.41. Thus, it can be concluded that the implementation of the Contextual Teaching and Learning (CTL) model can improve the mathematical learning outcomes of grade II students at State Elementary School 32 Tumampua VI.